Effects of photo-initiation and monomer composition onto performance of graft-copolymer based membrane adsorbers - Mohd Yusof, Abdul Halim; Mathias, Ulbricht (Elsevier, 2006)
Photo-initiated surface-selective graft copoly- merisation onto polypropylene (PP) microfiltration membranes is an improved method to prepare porous membrane adsorbers [1]. The potential versatility and economic value of this method motivated us to further investigate main parame- ters for control of membrane adsorber function- ality. In this work we studied the influence of photo initiator concentration and entrapping time in the initiator immobilization step and of monomer solution composition in the photo- grafting step. Benzophone (BP) dissolved in heptane was used in the photo initiator coating step. The functional monomer acrylic acid (AA), the diluent monomer acrylamide (AAm) and the cross-linker methylene bisacrylamide (MBAA) were used to prepare grafted copoly- mer layers with weak cation-exchange groups in the second step. For the characterization we focussed on the degree of grafting (DG) via gravimetry, ATR-IR spectroscopy, membrane permeability as a function of solution pH and ionic strength and dynamic protein binding capacities and recovery from membrane chro- matography experiments. Using the membranes with best performance, the separation of protein mixture was also investigated.